Effect of the Types and Percentages of Stabilizer on the Quality of Instant Garfish Condiment - Marchelina, Christine; Sinaga, Hotnida; Lubis, Linda Masniary (Talenta Publisher, 2020)
The purpose of this research was to determine the effect of stabilizer types and percentages on the quality of instant garfish condiment. The research used a group randomized design factorial with two factors, i.e.: types of stabilizer (CMC; Arabic gum; gelatin) and percentage of stabilizer (0.0%; 0.5%; 1%; 1.5%). The results showed that stabilizer types had a highly significant effect on water absorption index, water solubility index, vitamin C, and color index. Moreover, the stabilizer had no significant effect on organoleptic aroma and taste. In the meantime, stabilizer percentages had a highly significant effect on water absorption index, water solubility index, vitamin C, color index, and organoleptic aroma. However, the stabilizer percentages gave no significant effect on organoleptic taste. Interaction between the two factors had a highly significant effect on water absorption index and vitamin C and had a significant effect on color index. Furthermore, the interaction had no significant effect on water solubility index, organoleptic aroma and taste. The best treatment product was resulted from the use of 1.5% CMC as stabilizer.